2011
DOI: 10.1002/mc.21848
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb group protein EZH2‐mediated E‐cadherin repression promotes metastasis of oral tongue squamous cell carcinoma

Abstract: Enhancer of zeste homolog 2 (EZH2) is a critical component of the polycomb-repressive complex 2 (PRC2) that regulates many essential biological processes, including embryogenesis and many developmental events. The oncogenic role of EZH2 has recently been implicated in several cancer types. In this study, we first confirmed that the over-expression of EZH2 is a frequent event in oral tongue squamous cell carcinoma (OTSCC). We further demonstrated that EZH2 over-expression is correlated with advanced stages of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
60
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 25 publications
10
60
0
Order By: Relevance
“…A previous study revealed that EZH2 is a catalytic subunit of the epigenetic regulator PRC2, which trimethylates Lys27 of histone H3, leading to the silencing of target genes that are involved in numerous biological processes, including tumor progression (16). Overexpression of EZH2 has been detected in a range of types of cancer, and is associated with tumor malignancy (14,15) via the epigenetic silencing of tumor and metastasis suppressor genes (25,26). However, FHL1 downregulation was not significantly associated with clinicopathological characteristics of patients applied in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that EZH2 is a catalytic subunit of the epigenetic regulator PRC2, which trimethylates Lys27 of histone H3, leading to the silencing of target genes that are involved in numerous biological processes, including tumor progression (16). Overexpression of EZH2 has been detected in a range of types of cancer, and is associated with tumor malignancy (14,15) via the epigenetic silencing of tumor and metastasis suppressor genes (25,26). However, FHL1 downregulation was not significantly associated with clinicopathological characteristics of patients applied in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of EZH2 significantly correlated with tumor size, cervical lymph node metastasis, clinical stage and poor prognosis, and served as an independent prognostic indicator for patients with head neck cancer [23-25]. However, the in-depth investigations into the expression pattern of EZH2 and associated molecular mechanisms underlying TSCC development has been in infancy and remains to be further clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Tca8113 was previously established at Shanghai Jiaotong University (a generous gift from Professor Wantao Chen). 31 The Cal27, SCC9 and SCC25 cells were purchased from American Type Culture Collection (ATCC). Cancerous cell lines were grown in DMEM (Invitrogen) supplemented with 10% FBS (Gibco) and 100 units/ml penicillin and streptomycin, and maintained in a humidified incubator with 5% CO 2 at 37 1 C. The HDACis TSA and NaB were purchased from Sigma Aldrich (category number: T8552, B5887) and dissolved in DMSO or PBS as stocking solutions and diluted with culture medium upon addition into cells.…”
mentioning
confidence: 99%